Substitution Possibilities for Unpriced Natural Resources: Restricted Cost Functions for the Canadian Metal Mining Industry - Halvorsen, Robert; Smith, Tim R. (The Review of Economics and Statistics, 1986)
Robert Halvorsen, Tim R. Smith, Substitution Possibilities for Unpriced Natural Resources: Restricted Cost Functions for the Canadian Metal Mining Industry, The Review of Economics and Statistics, Vol. 68, No. 3 (Aug., 1986), pp. 398-405